DETECTION OF BUFFALO PREGNANCY ASSOCIATED GLYCOPROTEIN-1 GENE TRANSCRIPTS AT DIFFERENT STAGES OF PREGNANCY - SINGH, JEROME A; AGARWAL, S K; SARATH, S K; ARUNMOZHI, N (The Indian Journal of Animal Reproduction, 2011)
Pregnancy is established and maintained in response to a series of interactions between the conceptus andmaternal reproductive tract through a large family trophoctoderm proteins i.e. Pregnancy associated glycoprotein.PAG-1 gene has been characterized and its expression has been detected in many domestic, wild ruminants aswell as pigs but not in buffalo. In this study buffalo PAG-1 gene transcripts was PCR amplified during variousstages of pregnancy i.e. (Day 30, 50, 60, 70, 90, 110, 150 and full term). Moreover buffalo PAG-1 gene wascharacterized using EcoR !: as restriction enzyme showed the presence of the conserved site for EcoR I for everybinucleate specific PA Gs especially PAG-1. From the present study, it was found that buffalo Pregnancy AssociatedGlycoprotein-1 gene was expressed throughout gestation which could be detected qualitatively confirming theexpression of the buffalo Pregnancy Associated Glycoprotein-1 gene transcripts throughout pregnancy similar tocattle and other species.
Keywords: PAG1; Buffalo; Gene expression; Pregnancy